How Do Students Adapt in Response to Academic Failure? - Rola Ajjawi; David Boud; Nadine Zacharias; Mary Dracup; Sue Bennett (Student Success)
Ensuring student success has long been on the research agenda in higher education. In this study, we seek to understand if the changes students make in light of academic failure are consistent with this literature. Little is known about students who fail but subsequently persist in their studies. Through an online survey with students who had failed and persisted, we identified drivers for persistence and how students adapted in response to academic failure. Thematic analysis showed that the majority of students did not seek institutional support following academic failure but they did seek support from peers, family and friends. These adaptations occurred at multiple levels: dispositional, situational and institutional. Drivers reported were internal (desire to complete) and external (desire to meet expectations). Although the majority of our students showed positive adaptations following academic failure, a significant portion reported no changes to their academic strategies. The paper poses the question of how students who fail can be better supported to continue successfully.